THE EFFECT OF BIG FIVE PERSONALITY ON EMPLOYEE PERFORMANCE THROUGH BEHAVIOR ORGANIZATIONAL CITIZENSHIP IN DINAS SOCIAL SOUTH SULAWESI PROVINCE - Andi Sri Hermawan; Djabir Hamzah; Sumardi Lasise (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to explain and analyze: 1). The effect of extraversion on Organizational Citizenship Behavior of employees; 2). The effect of Neuroticism on the Performance of Organizational Citizenship Behavior of Employees; 3) The influence of Openness to Experiences on Organizational Citizenship Behavior for Employees; 4). The influence of Agreablenes on Organizational Citizenship Behavior for employees; 5). The effect of Conscientiousness on Employee Organizational Citizenship Behavior; 6). Direct and indirect directors extraversion of employee Performance; 7). The direct and indirect influence of neuroticism on Employee Performance; 8). The direct and indirect influence of Openness to Experiences on Employee Performance; 9). The direct and indirect influence of Employee Performance Agreablenes; 10). Direct and indirect effect of Conscientiousness on Employee Performance; 11). The effect of Organizational Citizenship Behavior on Employee Performance This type of research is quantitative research with SEM (Structural Equation Model) method which looked for the relationship between variables. While the steps were taken consisted of determining the structural model, followed by setting the measurement model, combining data and checking, pretest validity and reliability, determining the path analysis model, collecting models and analyzing with IBM-SPSS AMOS 22, testing the fit test model, if possible to re-check the model, and then interpreted the results of data processing. The results showed that: 1). The extract significantly affects OCB; 2). Neuroticism has a significant effect on OCB: 3). Openness to Experiences influence OCB; 4). Agreeableness has a significant effect on OCB; 5). Conscientiousness has no significant effect on OCB; 6). Direct extract does not have a significant effect on performance and has a significant indirect effect on performance; 7). Slim neuroticism has no significant effect on performance and has a significant indirect effect on performance; 8). Openness to Experiences directly has no significant effect on performance and indirectly significant effect on performance; 9) Agreeableness has a significant direct and indirect significant impact on performance; 10) Conscientiousness has no significant effect both directly and indirectly on performance; 11) OCB has a significant effect on performance.